Associations Between Adherence to Evidence-Based, Stroke Quality Indicators and Outcomes of Acute Reperfusion Therapy. Issue 11 (16th August 2022) - Ren, Nice; Ogata, Soshiro; Kiyoshige, Eri; Nishimura, Kunihiro; Nishimura, Ataru; Matsuo, Ryu; Kitazono, Takanari; Higashi, Takahiro; Ogasawara, Kuniaki; Iihara, Koji; ,
Abstract : Background: Quality indicators (QIs) are an accepted tool for measuring a hospital's performance in routine care. We examined national trends in adherence to the QIs developed by the Close The Gap-Stroke program by combining data from the health insurance claims database and electronic medical records, and the association between adherence to these QIs and early outcomes in patients with acute ischemic stroke in Japan. Methods: In the present study, patients with acute ischemic stroke who received acute reperfusion therapy in 351 Close The Gap-Stroke-participating hospitals were analyzed retrospectively. The primary outcomes were changes in trends for adherence to the defined QIs by difference-in-difference analysis and the effects of adherence to distinct QIs on in-hospital outcomes at the individual level. A mixed logistic regression model was adjusted for patient and hospital characteristics (eg, age, sex, number of beds) and hospital units as random effects. Results: Between 2013 and 2017, 21 651 patients (median age, 77 years; 43.0% female) were assessed. Of the 25 defined measures, marked and sustainable improvement in the adherence rates was observed for door-to-needle time, door-to-puncture time, proper use of endovascular thrombectomy, and successful revascularization. The in-hospital mortality rate was 11.6%. Adherence to 14 QIs lowered the odds of in-hospital mortality (odds ratio [95% CI], door-to-needle <60 min, 0.80 [0.69–0.93], door-to-puncture <90 min, 0.80 [0.67–0.96], successful revascularization, 0.40 [0.34–0.48]), and adherence to 11 QIs increased the odds of functional independence (modified Rankin Scale score 0–2) at discharge. Conclusions: We demonstrated national marked and sustainable improvement in adherence to door-to-needle time, door-to-puncture time, and successful reperfusion from 2013 to 2017 in Japan in patients with acute ischemic stroke. Adhering to the key QIs substantially affected in-hospital outcomes, underlining the importance of monitoring the quality of care using evidence-based QIs and the nationwide Close The Gap-Stroke program.